CROSS-REACTIVITY BETWEEN HARD TICK ANTIGENS - Almeida, APG; Bechara, G. H.; Varma, RMG (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
1. The present study was carried out to determine the target cells and tissues for anti-tick immunoglobulins using an indirect immunohistochemical technique.2. Sections in triplicate prepared from unfed ticks Rhipicephalus appendiculatus, R. evertsi and Amblyomma variegatum were used to assess the cross-reactivity of serum from guineapigs naturally infested with these tick species or immunized against them.3. The sections showed slight (+) to strong (++++) labelling of several structures in the tick body, e.g. salivary gland, gut lumen and malpighian tubules, depending on the serum used.4. The immune serum resulting from the immunization of guinea pigs with an extract of unfed nymphs of R. appendiculatus ticks showed the most intense cross-reactivity with the sections examined.
Keywords: IMMUNOLOGY; Ticks; SHARED ANTIGENS; Immunohistochemistry